DAMPAK KETIDAKADILAN GENDER SERTA RESPONS DAN PERLAWANAN TOKOH ERNA DALAM NOVEL MECAKI KATRESNAN ING SATENGAHE PERANG POLITIK KARYA TULUS SETIYADI: KAJIAN KRITIK SASTRA FEMINIS - Meilani Cindi Ambarwati; Krisna Pebryawan; Luwiyanto (JURNAL SKRIPTA, 2026)
This study analyzes the impact of gender injustice and the response and resistance of character Erna in the novel Mecaki Katresnan ing Satengahe Perang Politik by Tulus Setiyadi. A descriptive qualitative approach with feminist literary criticism was employed. Data comprising narrative quotations and dialogues were collected through reading, note-taking, and literature study, then analyzed using the interactive model of Miles, Huberman, and Saldana. Data validity was ensured through observational persistence, theory triangulation, and reference adequacy. Two main findings emerged: (1) the impacts of gender injustice experienced by Erna include deep psychological trauma from repeated sexual violence, internalization of stigma as a ruined woman embedded in the victim's self-concept, and social isolation due to absent support from family, law, and community; (2) Erna's resistance develops progressively from verbal resistance through threats of public exposure against Rafa, an active decision to leave home rejecting patriarchal construction, to a resolve to expose corrupt politicians as a transformation of trauma into collective political consciousness. This reflects the emergence of female agency, shifting the character from an object of oppression to a subject who reclaims her life narrative. This research contributes to feminist literary criticism in modern Javanese literature and is relevant for gender justice-based character education in secondary schools.